We're putting service first - IPMS poster, 1992 (London, 1992)
1992 1980-95 "We're putting service first - IPMS poster, 1992" [BW0067], 1992, Trades Union Congress Recruitment poster from the Institution of Professionals, Managers and Specialists showing scientific staff in the civil service.